Direct access colonoscopy in primary care: is it a safe and practical approach?. Issue 3 (August 2013) - Ahmed, J; Mehmood, S; Khan, SA; Rao, MM
Background: Implementation of colorectal cancer screening programme and provision of cancer service within certain timeframe has significantly increased the workload on endoscopy services. Direct access colonoscopy in primary care centers helps offload burden on conventional colonoscopy in secondary care, thereby reducing waiting times. The aim of this study was to assess the safety and efficacy of direct access colonoscopy service. Materials and methods: Provision of colonoscopy service in our healthcare trust was analysed retrospectively during a two-year period. Safety and feasibility of direct access colonoscopy was analysed against conventional colonoscopy. The groups were compared for findings at colonoscopy, procedural outcomes, and complications. Results: A total of 3468 colonoscopies were analysed. Of those, 1189(34.3%) were performed as direct access colonoscopy and 2279(65.7%) as conventional colonoscopy. No abnormality was detected in 408/1189(34.3%) and 825/2279(36.2%) patients in the direct access colonoscopy and conventional colonoscopy groups, respectively ( p  = 0.52). Colorectal cancer detection rate was similar between the groups; conventional colonoscopy vs direct access colonoscopy, 3.1% (68/2279) vs 3.2% (39/1189) ( p  = 0.85). However, there was significantly higher detection rate of polyps greater than 1 cm in conventional colonoscopy group compared to direct access colonoscopy group, 22.6%(518/2289) vs 12.6% (150/1189) ( p  = 0.02). Complication rates were comparable between the groups. Conclusion: Direct access colonoscopy in primary care centers is safe and feasible. Colorectal cancer detection remains comparable to that of conventional colonoscopy in secondary care despite relatively lower polyp detection rate.